120 Extent of Surgical Excision of the Vestibule Based on Positive CD117 and PGP9.5 Staining of Mast Cells in Women with Neuroproliferative Vestibulodynia. (1st May 2022) - Goldstein, I; Yee, A; Uloko, M; Goldstein, A
ABSTRACT: Introduction: Neuroproliferative vestibulodynia (NPV) is a poorly understood chronic debilitating sexual pain condition associated with severe vestibular allodynia and hyperalgesia. In patients with NPV, histopathology of surgical specimens from the usual posterior and right and left anterior locations (1:00 - 11:00 o'clock) has shown high densities of CD117 and PGP9.5 positive staining cells consistent with excessive mast cells and nerves. Such pathologic findings have justified the excision of this usual location of the vestibule. There is, however, a lack of consensus regarding the total extent of complete surgical excision for vestibulectomy. Some of our patients demonstrated pain at the 12:00 region and underwent concomitant 12:00 excision along with the usual vestibule location. We wished to study excised vestibular tissue at the 12:00 region for the presence/absence of CD117 and PGP9.5 positive staining cells. This pathologic finding has critical clinical implications as to the extent of the surgical excision. Objective: We assessed immunohistochemical densities of CD117 and PGP9.5 positive staining cells from the 12:00 region from each patient, comparing it to cells stained from posterior and left/right anterior vestibule. Methods: We studied specimens from 26 women (mean age 27 +/- 12 years) with the presumptive diagnosis of NPV based on positive vestibular cotton swab testing at 12:00 as well as 1:00, 3:00, 5:00, 6:00, 7:00, 9:00 and 11:00 locations who underwent complete vestibulectomy with vaginal advancement flap including the 12:00 region. Surgical specimens from the 12:00, the posterior and left/right anterior vestibule were prepared separately in formalin and embedded in paraffin blocks. Immunohistochemical staining using antibodies to CD117 and PGP 9.5 was performed on these blocks and sections cut for slides. These stained slides from multiple locations of the vestibule were examined and photographed using a Zeiss AxioCam HR high resolution digital microscope. The density of CD117 and PGP9.5 positive cells were determined by counting the number of dark brown stained cells per high-power field (HPF = x 20 magnifications). Based on the literature, control subjects have values of 8 mast cells or less per HPF. Results: All 26 patients had elevated densities of CD117-positive cells in vestibular epithelium/stroma in the 12:00 (mean density 51 +/- 19 per HPF) as well as posterior and left/right anterior vestibule (mean density 47 +/- 18 per HPF). All 26 patients had high densities of PGP9.5-positive cells noted in vestibular stroma in the 12:00 (mean density 36 +/- 23 per HPF) and posterior and left/right anterior vestibule (mean density 38 +/- 22 per HPF). Conclusions: In 100% of these patients NPV, the 12:00 region of the vestibule contained an increased number of CD117 and PGP9.5 positive staining cells similar to the posterior and left/right anterior vestibule. When performing a vestibulectomy in patients with positive cotton-tip swab testing including the 12:00, excision of the 12:00 vestibule should be considered to optimize treatment. Disclosure: Work supported by industry: no.